INFLUENCE OF CALCIUM CHOLORIDE ON PHYSICAL CHARACTERISTICS AND SOFT ROT INCIDENCE ON FRUIT OF APPLE CULTIVARS - I. Jan; A. Rab; M. Sajid (Journal of Animal and Plant Sciences, 2013)
The research on influence of calcium choloride on physical characteristics and soft rot incidence in apple cultivars was carried out at Horticulture Postharvest Laboratory, The University of Agriculture Peshawar-Pakistan during 2009-10. The fruits were harvested from apple cultivars: Royal Gala, Mondial Gala and Golden Delicious at commercial maturity stage at Matta, Swat. The experiment was laid out in completely randomized design (CRD) with factorial arrangement having twelve treatment combinations. The fruits were treated with 0 and 9 % CaCl2 solution for the period of 12 minutes and stored for the period of 150 days at 5±1°C with 60-70 % relative humidity. Apple cultivar Royal Gala had the highest juice content (59.20 %) and firmness (5.46 kg/cm2). Mondial Gala had the least weight loss (1.55 %). Percent weight loss and soft rot increase while, juice content, firmness and density of fruit declined during storage. The application of CaCl2 significantly decreased percent weight loss (1.16 %) and soft rot (1.41 %), while juice content (57.58 %), firmness (5.62 kg/cm2) and density of fruit (0.78 g/cm3) increased with CaCl2 solution.
Keywords: Apple; cultivars; calcium chloride; physical characteristics; storage; soft rot